2019
DOI: 10.1111/ijfs.14159
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ultrasound‐assisted frying on the physiochemical properties and microstructure of fried meatballs

Abstract: Summary The aim of this study was to investigate the effects of power ultrasound (0, 200, 400, 600 and 800 W, 20 kHz) on the quality of fried meatballs. The frying time and frying temperature were also considered as fixed factors. The meatballs were fried for 8, 12 and 16 min at 120, 140 and 160 °C. Results showed that the ultrasonic groups saved about 1 to 3 min than the control group to 80 °C. Hardness, springiness, cohesiveness and chewiness of fried meatballs were significantly different among different ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…The cooking process can strongly impact the texture, color, and other significant quality factors of the final product [ 4 ], which are crucial consumer satisfaction-related attributes. During heat processing, collagen disintegration or protein denaturation can cause the partial or complete decomposition of the muscle fiber structure; moreover, the springiness and hardness were found to be decreased, in addition to other textural parameters [ 5 ]. Zeng et al [ 6 ] observed that cooking treatment could induce serious shrinkage of muscle fibers of salted-dried fish, resulting in textural changes due to increased sample springiness, as well as reduced hardness and chewiness.…”
Section: Introductionmentioning
confidence: 99%
“…The cooking process can strongly impact the texture, color, and other significant quality factors of the final product [ 4 ], which are crucial consumer satisfaction-related attributes. During heat processing, collagen disintegration or protein denaturation can cause the partial or complete decomposition of the muscle fiber structure; moreover, the springiness and hardness were found to be decreased, in addition to other textural parameters [ 5 ]. Zeng et al [ 6 ] observed that cooking treatment could induce serious shrinkage of muscle fibers of salted-dried fish, resulting in textural changes due to increased sample springiness, as well as reduced hardness and chewiness.…”
Section: Introductionmentioning
confidence: 99%
“…The bromelain might degrade partial oxidase and reductase, resulting in changes in the value of a* (Faustman et al., 2010 ). Fat and the oxidative polymerization of carbohydrates could significantly affect the b* of meat (Wang et al., 2019 ). The reduced values of b* might be due to the antioxidant properties of peptides and amino acids from the protein degradation by bromelain thus decreasing the oxidation of fat, protein, and carbohydrates (Borrajo et al., 2020 ; Wang et al., 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…e texture profile analysis of 10 meatballs before and after frying (DFF and HAF) was performed in a CT3 Texture Analyzer (Brookfield Co., Ltd. USA), with an adjusted procedure of Wang et al [16]. Fried meatball samples were cut uniformly prior to analysis.…”
Section: Texture Profile Analysismentioning
confidence: 99%
“…Ateba and Mittal [15] investigated the process of coat evolution and attributes of meatballs suffering from frying. Wang et al [16] found that ultrasonic-aided frying could improve some physicochemical indexes of beefballs. Zhang et al [17] further proved that ultrasonic-aided frying could improve the flavor profiles of meatballs.…”
Section: Introductionmentioning
confidence: 99%